Paradise Now: Image Restoration of the Palestinian Society - Abu taleb, Hala (Dirasat: Human and Social Sciences, 2019)
This paper sheds light on Hani Abu Assad’s movie Paradise Now. The movie is seen as an alternative resistance method through which Abu Assad challenges the stereotypical image of Arabs. The movie presents Arabs, particularly Palestinians within a new identity that is closer to reality as opposed to the mythical one often promoted by Hollywood. The director chooses to follow the last days of two "suicide bombers" in order to expose part of the harsh realities that these young men and women go through as normal people facing dozens of cultural, economical and political challenges. This paper aims at focusing on such cinematic attempts that utilizes art in order to spread deeper understanding of the Other and a clearer vision of mutual existence.